The cult of St Thomas Becket in the Plantagenet world, c.1170-c.1220 - Webster, Paul; Gelin, Marie-Pierre (The Boydell Press, 2016)
Thomas Becket - the archbishop of Canterbury cut down in his own cathedral just after Christmas 1170 - stands amongst the most renowned royal ministers, churchmen, and saints of the Middle Ages. He inspired the work of medieval writers and artists, and remains a compelling subject for historians today. Yet many of the political, religious, and cultural repercussions of his murder and subsequent canonisation remain to be explored in detail. This book examines the development of the cult and the impact of the legacy of Saint Thomas within the Plantagenet orbit of the late twelfth and early thirteenth centuries - the "Empire" assembled by King Henry II, defended by his son King Richard the Lionheart, and lost by King John. Traditional textual and archival sources, such as miracle collections, charters, and royal and papal letters, are used in conjunction with the material culture inspired by the cult, to emphasise the wide-ranging impact of the murder and of the cult's emergence in the century following the martyrdom. From the archiepiscopal church at Canterbury, to writers and religious houses across the Plantagenet lands, to the courts of Henry II, his children, and the bishops of the Angevin world, individuals and communities adapted and responded to one of the most extraordinary religious phenomena of the age